Junctional Epidermolysis Bullosa: Allelic Heterogeneity and Mutation Stratification for Precision Medicine - Condrat, Irina; He, Yinghong; Cosgarea, Rodica; Has, Cristina (Frontiers in Medicine, 2019)
Abstract Junctional epidermolysis bullosa (JEB) is a hereditary blistering disease caused by reduced dermal-epidermal adhesion due to deficiencies of one of the proteins, laminin-332, type XVII collagen, integrin 64 or integrin 3. Significant progress has been achieved in the development of therapies for EB, such as bone-marrow transplantation, local or systemic injections with fibroblasts or mesenchymal stromal cells, readthrough of premature termination codons, or exon skipping. These were tailored in particular for dystrophic EB, which is caused by type VII collagen deficiency and have not yet reached broad clinical practice. Recently, pioneering combined gene and stem cell therapy was successful in treating one boy with junctional EB. Beside this exclusive approaches, no specific therapy to amend the major clinical features, skin and mucosal blistering and non-healing wounds is available to date. Here we extend the mutational spectrum of junctional EB, provide a stratification of COL17A1 mutations and discuss potential molecular therapeutic approaches